Antimicrobial and Cytotoxicity Activities of Medicinal Plants against Salmonella gallinarum Isolated from Chickens - Mwanaisha Mkangara; Fulgence N. Mpenda (Veterinary Medicine International)
Medicinal plants have been the good source of treatment for different ailments of humans as well as animals for centuries. However, in Tanzania, few plants were investigated for their efficacy against various diseases of chickens. In the present study, four medicinal plants were investigated against Salmonella gallinarum isolated from chickens. The minimum inhibitory concentration (MIC) using the broth microdilution methods and minimum bactericidal concentration (MBCs) were used to evaluate the activities of plants against chicken salmonellosis. For the safety of chickens against the toxicity of plants, the cytotoxicity assay was determined using a brine shrimp lethality test. Aloe secundiflora leaf ethyl acetate (ALEA), Aloe rabaiensis leaf methanolic (ArM), Aloe rabaiensis leaf ethyl acetate (ArLEA), and Punica granatum leaf ethyl acetate (PGLEA) extracts exhibited the highest MIC (0.3906 mg/mL) and MBC (3.125 mg/mL), respectively. The Dolichos kilimandscharicus tuber ethyl acetate (DTEA) and Dolichos kilimandscharicus tuber pet ether (DTPE) extracts displayed MIC of 1.563 mg/mL and 12.50 mg/mL and MBC of 12.50 mg/mL and 25.50 mg/mL, respectively. The highest LC50 values exhibited in Dolichos kilimandscharicus ranged from 7.937 × 10−4 mg/mL to 7.242 × 10−2 mg/mL for pet ether and methanolic extracts, respectively, while ALEA extract exhibited LC50 of 7.645 × 10−3 mg/mL. Generally, the extracts with MIC 0.3906 mg/mL and MBC 3.125 mg/mL demonstrated the highest antibacterial activity with low toxicity efficient to manage chicken salmonellosis. Dolichos kilimandscharicus, which exhibited higher toxicity, warrants further investigation on insecticidal and anticancer agents.